Anti-CD19 CAR-T cell therapy in relapsed/refractory t(8;21) acute myeloid leukemia with aberrant CD19 expression - Zhang, Xiaomin; Wang, Lixin; Qiao, Jingqiao; Wang, Shuhong; Wang, Lijun; Liu, Lian; Qin, Jiading; Chen, Ziren; Huang, Wenfa; Zheng, Yuanyuan; Peng, Huixin; Mei, Junhui; et al. (Frontiers in Immunology, 2025)
BackgroundT (8; 21) acute myeloid leukemia (AML) is a special type of acute leukemia, and exhibits a heterogeneous prognosis, with a long-term relapse rate of about 40%. Once t(8; 21) AML patients experience relapse, they have an extremely poor prognosis, with a 5-year overall survival rate of less than 15%. Therefore, it is crucial to develop effective strategies to improve the prognosis of relapsed/refractory (R/R) t(8; 21) AML. CD19 is a specific B-cell surface marker, but it is aberrantly expressed in 50-80 % of t(8; 21) AML patients. CAR-T cells targeting aberrant cell-surface antigens could induce the depletion of tumor cells without the destruction of hematopoiesis. Therefore, CD19 might be a promising target for CAR-T cell therapy in R/R t(8; 21) AML with aberrant CD19 expression. The present study is aimed to explore the efficacy and safety of CD19 CAR-T cell therapy in R/R t(8;21) AML with aberrant CD19 expression.MethodsIn the present study, 3 R/R t(8;21) AML patients with aberrant CD19 expression were enrolled. After lymphodepleting chemotherapy, 3 patients received autologous CAR-T cell infusion at a dose of 1.0 × 10^6 cells/kg, 2.0 × 10^6 cells/kg, and 2.0 × 10^6 cells/kg, respectively.ResultsThey all achieved CD19 negativity approximately half a month after CD19 CAR-T cell infusion. These indicate CD19 CAR-T cell therapy is effective in R/R t(8;21) AML with aberrant CD19 expression. However, patient 1 and patient 2 rapidly relapsed within 3 months after CD19 CAR-T cell therapy. Subsequently, patient 1 received allogeneic hematopoietic stem cell transplantation (allo-HSCT). Fortunately, patient 1 achieved mCR 2 months after allo-HSCT.ConclusionConsidering the short-term remission of CD19 CAR-T cell therapy in R/R t(8;21) AML, allo-HSCT might be performed as soon as possible to consolidate the efficacy of CAR-T cell therapy and reduce the risk of relapse.